Developing skills of professionally-oriented reading at the lessons of foreign language in non-language high schools - Musiichuk, S. M. (Visnyk of Vinnytsia Politechnical Institute, 2014)
The article examines the main methods of teaching professionally-focused reading at the lessons of foreign language in non-language high schools. The main types of working with the specialized texts and recommendations for doing exercises before and after the texts are given in the paper.